Britain and the working time regulations - Blair, Alasdair; Leopold, John; Karsten, Luchien (2001)
It is now over a year since the Working Time Regulations entered force in Britain on 1 October 1998, during a period when the government also introduced the minimum wage. But whereas that piece of legislation appears to have faded away into the background of British industrial relations, the Working Time Regulations continue to remain a central topic. Based on a survey of British companies and organisations, this article reviews the implementation of the legislation and examines the scope of coverage. It finds that the failure of the Labour government to consult the social partners - employer and employee representatives - resulted in business being unprepared for the Regulations. The article also notes that the manner in which this legislation was introduced has meant that many of the employees who were working excessive hours continue to do so. - Reproduced
Keywords: Working time